Modeling the impacts of hot drought on forests in Texas - Lawal, Shakirudeen; Costanza, Jennifer; Koch, Frank H.; Scheller, Robert M. (Frontiers in Forests and Global Change, 2024)
Under climate change, drought is increasingly affecting forest ecosystems, with subsequent consequences for ecosystem services. An historically exceptional drought in Texas during 2011 caused substantial tree mortality. Here, we used 2004 -2019 Forest Inventory and Analysis (FIA) data and state-wide weather data to examine the climatic conditions associated with this elevated tree mortality. We measured moisture extremes (wet to dry) using the Standardized Precipitation Evapotranspiration Index (SPEI) at two timescales (12-and 36-month). We quantified heat wave severity using the Heat Wave Magnitude Index daily (HWMId) over the same period. We performed statistical modeling of the relationship between tree mortality and these indices across four Texas regions (Southeast, Northeast, North Central, and South) and for prominent tree genera (Pinus, Juniperus, Quercus, Liquidambar, Prosopis, and Ulmus) as well as selected species: Quercus stellata, Q. virginiana, and Q. nigra. The highest tree mortality was observed between 2011 and 2013. We found similarity in the trends of the 12and 36-month SPEI, both of which exhibited more extreme negative intensities (i.e., drought) in 2011 than other years. Likewise, we found that the extreme heat experienced in 2011 was much greater than what was experienced in other years. The heat waves and drought were more intense in East (i.e., Southeast and Northeast) Texas than Central (i.e., North Central and South) Texas. In gradient boosted regression models, the 36-month SPEI had a stronger empirical relationship with tree mortality than the 12-month SPEI in all regions except South Texas, where HWMId had more influence than SPEI at either timescale. The correlations between moisture extremes, extreme heat, and tree mortality were high; typically, mortality peaked after periods of extreme moisture deficit rather than surplus, suggesting that the mortality was associated with hot drought conditions. The effects of extreme heat outweighed those of SPEI for all tree genera except oaks (Quercus). In summary, we identified risks to Texas forest ecosystems from exposure to climate extremes. Similar exposure can be expected to occur more frequently under a changing climate.